How to breathe : 25 simple practices for calm, joy, and resilience - Neese, Ashley, 1980- (Ten Speed Press, 2019)
"A simple guide to breathwork by a lauded expert that takes you through 25 simple practices for everyday situations, such as de-stressing, managing anger, falling asleep, connecting with others, and more. In How to Breathe, breathwork expert Ashley Neese gives practical guidance for channeling the power of your breath to help you tackle common challenges with mindfulness and serenity. The book first introduces you to the foundations of breathwork, outlining the research-supported benefits of the practice and explaining how the breath relates to emotions and resilience. Neese then offers 25 customized practices that she has created for clients over the last decade. Each practice features an introduction explaining the origin, benefits, and purpose of the breathwork, followed by step-by-step instructions and post-practice notes. With transporting photography and modern design, How to Breathe shows how small exercises can have a huge impact on daily health and happiness"--